Vancomycin-nanofunctionalized peptide-enriched silk fibroin to prevent methicillin-resistant Staphylococcus epidermidis-induced femoral nonunions in rats - Bottagisio, Marta; Palombella, Silvia; Lopa, Silvia; Sangalli, Fabio; Savadori, Paolo; Biagiotti, Marco; Sideratou, Zili; Tsiourvas, Dimitris; Lovati, Arianna B. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Implant-related infections and infected fractures are significant burdens in orthopedics. Staphylococcus epidermidis is one of the main causes of bone infections related to biofilm formation upon implants. Current antibiotic prophylaxis/therapy is often inadequate to prevent biofilm formation and results in antibiotic resistance. The development of bioactive materials combining antimicrobial and osteoconductive properties offers great potential for the eradication of microorganisms and for the enhancement of bone deposition in the presence of infections. The purpose of this study is to prevent the development of methicillin-resistant S. epidermidis (MRSE)-infected nonunion in a rat model. Methods To this end, a recently developed in our laboratories bioactive material consisting of antibiotic-loaded nanoparticles based on carboxylic acid functionalized hyperbranched aliphatic polyester (CHAP) that are integrated into peptide-enriched silk fibroin sponges with osteoconductive properties (AFN-PSF) was employed, whose biocompatibility and microbiological tests provided proof of its potential for the treatment of both orthopedic and dental infections. In particular, non-critical femoral fractures fixed with plates and screws were performed in Wistar rats, which were then randomly divided into three groups: 1) the sham control (no infection, no treatment); 2) the control group, infected with MRSE and treated with peptide-enriched silk fibroin sponges incorporating non-drug-loaded functionalized nanoparticles (PSF); 3) the treated group, infected with MRSE and treated with peptide-enriched silk fibroin sponges incorporating vancomycin-loaded functionalized nanoparticles (AFN-PSF). After 8 weeks, bone healing and osteomyelitis were clinically assessed and evaluated by micro-CT, microbiological and histological analyses. Results The sham group showed no signs of infection and complete bone healing. The PSF group failed to repair the infected fracture, displaying 75% of altered bone healing and severe signs of osteomyelitis. The AFN-PSF treated group reached 70% of fracture healing in the absence of signs of osteomyelitis, such as abscesses in the cortical and intraosseous compartments and bone necrosis with sequestra. Discussion AFN-PSF sponges have proven effective in preventing the development of infected nonunion in vivo. The proposed nanotechnology for local administration of antibiotics can have a significant impact on patient health in the case of orthopedic infections.